Modeling Deformation of Spur Gear - Lyashenko, Vyacheslav; Rudenko, Diana (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2021)
In The work considers 11 types of gears, features of their design and application. Analysis of gears designs is carried out, since shape of teeth directly affects process of teeth gearing, and this, in turn, affects load, which causes deformation of elements. 3D model of spur gear was created in ANSYS system. The work was limited by analyzing problem from point of view of gear wheels’ deformation, which were made of 40L carbon steel and carbon composite material. As a result, finite element modeling and analysis of gears using ANSYS system was carried out.